Image-Guided Radiotherapy and -Brachytherapy for Cervical Cancer - Dutta, Suresh; Nguyen, Nam Phong; Vock, Jacqueline; Kerr, Christine; Godinez, Juan; Bose, Satya; Jang, Siyoung; Chi, Alexander; Almeida, Fabio; Woods, William; Desai, Anand; David, Rick; et al. (Frontiers in Oncology, 2015)
Conventional radiotherapy for cervical cancer relies on clinical examination, 3-dimensional conformal radiotherapy (3D-CRT), and 2-dimensional intracavitary brachytherapy. Excellent local control and survival have been obtained for small early stage cervical cancer with definitive radiotherapy. For bulky and locally advanced disease, the addition of chemotherapy has improved the prognosis but toxicity remains significant. New imaging technology such as positron emission tomography (PET) and magnetic resonance imaging (MRI) has improved tumor delineation for radiotherapy planning. Image-guided radiotherapy (IGRT) may decrease treatment toxicity of whole pelvic radiation because of its potential for bone marrow, bowel, and bladder sparring. Tumor shrinkage during whole pelvic IGRT may optimize image-guided brachytherapy (IGBT), allowing for better local control and reduced toxicity for patients with cervical cancer. IGRT and IGBT should be integrated in future prospective studies for cervical cancer.